Forster’s moral vision : an examination of the religious imagery in Edward Morgan Forster’s fiction. - Leong, Keith Yan-Hao. (2013)
The bulk of Edward Morgan Forster's fiction is concerned with various social restrictions that, in his view, inhibit moral freedom. He commonly approaches this issue by exposing the causes and effects of these social restrictions through juxtaposition. This, however, becomes complicated in his fiction that deal with religion. Consequently, this essay aims to examine Forster's use of religion to determine what his view of religion is, and how it accords with his general moral concerns. It will argue that Forster has a conflicted view of religion because he sees on the one hand its moral restrictiveness and logical absurdity, and on the other its potential for moral emancipation, grounding, and linguistic transcendence.